Postoperative adjuvant transarterial chemoembolization improves outcomes of hepatocellular carcinoma associated with bile duct tumor thrombus: a propensity score matching analysis. Issue 4 (April 2022) - Chen, Zhen-Hua; Feng, Jin-Kai; Sun, Ju-Xian; Wu, Jia-Yi; Guo, Wei-Xing; Shi, Jie; Wei, Yong-Gang; Zhou, Jian-Yin; Zhang, Zhi-Bo; Yan, Mao-Lin; Cheng, Shu-Qun
Abstract: Background: Surgical resection is the primary treatment for hepatocellular carcinoma (HCC) with bile duct tumor thrombus (BDTT). This study was conducted to investigate the efficacy of postoperative adjuvant TACE (PA-TACE) in patients with HCC and BDTT. Methods: Data from patients who underwent surgery for HCC with BDTT at two medical centers were retrospectively analyzed. The survival outcomes of patients who were treated by hepatic resection followed by PA-TACE were compared with those of patients who underwent surgery alone. Propensity score matching (PSM) analysis was performed with a 1:1 ratio. Results: Of the 308 consecutively enrolled HCC patients with BDTT who underwent surgical resection, 134 underwent PA-TACE whereas 174 underwent surgery alone. From the initial cohort, PSM matched 106 pairs of patients. The OS and DFS rates were significantly better for the PA-TACE group than the surgery alone group (for OS: before PSM, P = 0.026; after PSM, P = 0.039; for DFS: before PSM, P = 0.010; after PSM, P = 0.013). Conclusion: PA-TACE was associated with better survival outcomes than surgery alone for patients with HCC and BDTT. Prospective clinical trials are warranted to validate the beneficial effect of PA-TACE on HCC patients associated with BDTT.